2021
DOI: 10.1111/bjd.19876
|View full text |Cite
|
Sign up to set email alerts
|

Biologics utilization for psoriasis is lower in black compared with white patients

Abstract: provided by hair styles in women. Human papillomavirus infection and/or systemic immunosuppression are additional risk factors for SCC; however, it is unclear whether they influence SCC development differently regarding face region or sex. 2 Melanoma distribution on the face may differ by sex. In two studies, 59Á8% and 71Á8% of facial melanoma cases were distributed on the cheek in female patients as compared with 48Á8% and 43Á6%, respectively, in male patients. 6,7 Although protection from hair can help decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In observational studies of patients with psoriasis, baseline characteristics are often significantly different across racial/ethnic groups [21][22][23][24][25]. A longer disease duration was observed for white patients with psoriasis (n = 21) than for Latino patients (n = 21; mean duration: 24.9 vs. 15.7 years; P = 0.01) in a cross-sectional study of patients screened for psoriasis clinical trials at an academic medical center in California [21].…”
Section: Differences In Baseline Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In observational studies of patients with psoriasis, baseline characteristics are often significantly different across racial/ethnic groups [21][22][23][24][25]. A longer disease duration was observed for white patients with psoriasis (n = 21) than for Latino patients (n = 21; mean duration: 24.9 vs. 15.7 years; P = 0.01) in a cross-sectional study of patients screened for psoriasis clinical trials at an academic medical center in California [21].…”
Section: Differences In Baseline Patient Characteristicsmentioning
confidence: 99%
“…An analysis of electronic health records (EHRs) in the US found that Hispanic/Latino patients with psoriasis ( n = 201) were older at diagnosis than white patients ( n = 3604; expected median age: 58 vs. 56 years; P = 0.04), but other non-white patients (i.e., not Black or Hispanic/Latino; n = 198) were younger than white patients (54 vs. 56 years; P < 0.001) [ 22 ]. Average age also varied across racial groups (white [ n = 4016]: 56.2, Black [ n = 291]: 54.8, other race [ n = 106]: 53.4 years; P = 0.07) in a study of medication use in patients with psoriasis at an academic medical center in Missouri [ 23 ]. A cross-sectional study of exacerbating factors of psoriasis at an academic medical center in California reported that the mean age at baseline differed across racial/ethnic groups (white [ n = 549]: 48.49, Asian [ n = 227]: 44.23, Hispanic [ n = 75]: 46.16 years; P = 0.006), as did body mass index (white: 26.28, Asian: 26.80, Hispanic: 29.42; P = 0.013) [ 25 ].…”
Section: Challenges Associated With the Diagnosis Of Psoriasis In Peo...mentioning
confidence: 99%
“…As our review focused on biologics, it is worth highlighting that prescription of biologics for indications such as psoriasis and rheumatoid arthritis is dependent on disease severity among other clinical and patient-specific factors [ 70 , 71 ]. Although the available literature from the USA shows that certain health conditions for which biologics are indicated are more prevalent in Caucasians compared to African Americans, Black patients often present with worse disease severity [ 10 ]. A statistically significant greater severity of immunological mediated conditions between Caucasians in Canada compared to those of African descent would necessitate a greater need for biologic therapy, hence contributing to apparent differences in biologic usage between these ethnic groups.…”
Section: A Way Forward: Recommendations For Key Stakeholdersmentioning
confidence: 99%
“…Another study found that Black patients with moderate-to-severe psoriasis were 70% less likely to receive biologics than White patients [ 9 ]. In addition, Black patients often present with worse disease severity [ 10 ]. As such, the difference in autoimmune and inflammatory disease prevalence between Whites and Blacks can only account for some of the disparity in biologic usage.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, in a retrospective study of 4413 systemically treated psoriasis patients, biologic utilization was lower in Blacks (51.9%) and other racial minorities (46.2%) versus in Whites (62.2%) (P \ .05). 4 Interracial or ethnic variability affects the exposure or response to approximately one-fifth of newly Food and Drug Administration-approved medications. 5 Ethnoracial differences in NP disease severity treatments has not been adequately explored but merit further study.…”
mentioning
confidence: 99%